(untitled) (Fiep Bulletin - online, 2011)
This work is a theoretical deductive study, of reflective nature, compound by bibliographic and documental research, under the focus of the qualitative approach. Tried to know the legislative and juridical and legislative contributions about the elder autonomy according to article number 1,641 of Brazilian Civil Code that forbids wedding for elderly people in universal communion of possessions. This work is about a study of the process of aging by the point of view of nursing, that emphasizes the autonomy of the people to choose the better of their lives, followed by a brief analyses of points of the law that treat of communion of goods between consorts. In the sequence of this work, presents material unconstitutionality of the cited article of Brazilian Civil Code, reasoning its unreasonableness and the prevailing of the docket 377. This subject is like that which there is a lack of understanding between the axiom and the jurisprudence, what recommends a wide review on the subject in respect to dignity of ones that are considered old people and can decide what to do about their own social, familiar and close lives.